THE ROLE OF QUALITY-MAKING WEIGHTS IN THE WORK ”MEHROBDAN CHAYON” - Adahamjon Umarov; Fotimaxon Mamtaliyeva (Research Focus International Scientific Journal, 2023)
In the lexicon of the Uzbek language, all-Arabic words form the majority. Especially in the lexicon, the amount of words belonging to the noun phrase category is high. They have their own semantic features. Arabic words represent more scientific, religious, moral, educational, abstract concepts